Identification of Water Quality and Heavy Metal Content at Tributary in Kletek Village, Sidoarjo - Tyastirin, Esti (International Conference on Sustainable Health Promotion, 2018)
The water ‘s tributary of Kletek Village, have characteristics not only close to residential areas but also along the main line between Sidoarjo and Krian-Mojokerto. Water quality measurements and heavy metal analyzes were performed at three observation statutes, with each station, consisting of 3 sampling points. Heavy metals analysis was conducted by the AAS method (Atomic Absorption Spectrophotometer). Obtained average levels of metal Pb and Cu at Water bodies in the Village Kletek that is equal to 2.9 mg/L and 0.14 mg/L. Each metal content has exceeded the standard quality limit with 1 mg/L and 0.1 mg/L values. Water Quality is  pH 7,  BOD 14,52 mg/L dan COD 118.57mg/L.